Modified Ant Colony Optimization (ACO) Algorithm for Routing in Vehicular Adhoc Networks - Giridhar, Koppisetti; Ananth, Dr. C Anbu (International journal of innovative technology and exploring engineering, 2019)
Vehicular Ad hoc Network (VANET) is divided as Mobile Ad-hoc Networks (MANETs) application which comprises the capability to offer Intelligent Transportation System (ITS) and to enhance road safety. VANET has many difficulties that various from instability problem that gives higher topological change and higher energy utilization with many advantages. The main aim to construct a route optimal path technique is to reduce the probability of linkage failure and decrease the node energy utilization within the network. ACO heuristic for vehicle routing is proposed in this paper. In this method mobility prediction is employed for stability of network and to reduce the utilized energy two-tier mechanism is employed by Location Aided Routing (LAR) protocol. The simulation outcomes in Network simulator 2 of the proposed method enhanced the node energy utilization within the network and it takes lower energy.